Компьютерная оценка температуры вспышки алканов - Жумабеков, Ж.М.; Жукова, А.Ю. (My University, 2013)
This paper presents the modeling flash alkanes using descriptors generated by the program Dragon. The estimation of the values of the flash for 54 previously untested substances.